Heat treatments hardening effect on Ni–Al composite electrodeposits. (1st February 2019) - Offoiach, R.; Lekka, M.; Johanns, K. E.; Fedrizzi, L.
ABSTRACT: Pure Ni galvanic coatings show good mechanical properties at room temperature but exhibit a progressive decrease by increasing the temperature due to the recrystallisation. A possible solution to hinder the recrystallisation is the co-electrodeposition of metal particles which could lead to the formation at high temperature of Ni alloy coatings with higher mechanical properties. Ni matrix composite deposits containing either micro (4 μm) or nano (130 nm) particles of Al were produced in a parallel plate geometry. The deposits were characterised regarding their microstructure both prior and after heat treatments for 3 h at 400, 600 and 800°C in order to evaluate the formation of Ni/Al phases. This work focused on the evaluation of the hardness on coatings cross-section by means of Vickers microhardness and Berkovich nano-indentation mapping. The results obtained with the two methods have been compared and correlated to the microstructural modifications in order to understand the hardening mechanisms.